Sequential Release HydroLipo System for STING Gene Epigenetic Reprogramming and Immune Activation in Glioblastoma - Hao Yu; Wenjing Liu; Kaikai Ding; Jiangjie Wu; Cheng Wang; Siyuan Wang; Lingyun Wu; Qiuying Tang; Xin Yin; Kan Jiang; Danfang Yan; Xu Wang; et al. (Advanced Science)
Abstract Glioblastoma (GBM) remains a daunting oncological challenge because of its aggressive nature and resistance to conventional therapies. Inhibition of the intrinsic STING pathway in GBM hampers the effectiveness of immunotherapies. To overcome this clinical limitation, a Sequential Release HydroLipo System (SRHLS) is developed, in which hydrogels and nanoparticles are combined for controlled drug release. The SRHLS sequentially released decitabine and STING agonists, thereby correcting STING signaling dysfunction through epigenetic reprogramming and enhancing antitumor immunity. According to in vitro and in vivo experiments, the SRHLS reshaped the tumor microenvironment and markedly inhibited tumor growth, recurrence, and metastasis. These findings underscore the potential of the SRHLS as a promising therapeutic strategy for GBM.